Knockdown of antizyme inhibitor decreases prostate tumor growth in vivo - Olsen, R.R.; Chung, I.; Zetter, B.R. (2012)
The endogenous protein antizyme inhibitor (AZI) is a potential oncogene which promotes cell growth by both inhibiting antizyme (AZ) activity and releasing ornithine decarboxylase (ODC) from AZ-mediated degradation. High levels of ODC and polyamines are associated with numerous types of neoplastic transformation, and the genomic region including AZI is frequently amplified in tumors of the ovary and prostate. To determine whether AZI functionally promotes prostate tumor growth, we made PC3M-LN4 (human) and AT6.1 (rat) cancer cell lines stably expressing shRNA to knockdown antizyme inhibitor 1 (AZI). AZI knockdown was confirmed by western blot, quantitative real-time PCR, and immunofluorescence. To examine the ability of these cells to form tumors in vivo, 1 x 10(6) cells were injected subcutaneously into nude mice either with (PC3M-LN4) or without (AT6.1) Matrigel. Tumor growth was measured two times per week by caliper. We found that cells in which AZI levels had been knocked down by shRNA formed significantly smaller tumors in vivo in both human and rat prostate cancer cell lines. These results suggest that not only does AZI promote tumor growth, but also that AZI may be a valid therapeutic target for cancer treatment.